Post OP Analgesic Effect of Transabdominal Block in Patients Undergoing Elective Ceaserian Section - Ayesha Saleem, Abdullah Saleem, Waqas Anjum, Yasmeen Azeem, Salma Sadia, Khushboo Chandio (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The management of postoperative pain, especially following abdominal surgeries, remains a pivotal challenge in clinical practice. The utilization of a transabdominal plane (TAP) block has recently emerged as a promising technique in achieving effective postoperative pain control. This study aimed to rigorously evaluate the analgesic efficacy of the TAP block in comparison with a control group not receiving the block, employing standardized Visual Analog Scale (VAS) scores and additional postoperative analgesic requirements as the primary outcome measures. Methods: A total of 50 patients undergoing abdominal surgery were randomly assigned to two groups: TAP block (n=25) and control (n=25). The TAP group received a specific dose of bupivacaine, while the control group received n/saline. Pain intensity was quantitatively assessed using VAS scores at 2, 6, 12, and 24 hours postoperatively. The requirement for additional postoperative analgesics was also recorded and compared between groups. Results: The TAP block group demonstrated consistently and significantly lower VAS scores across all time intervals measured, with mean differences ranging from 1.7 to 2.7 (p<0.001). Additionally, the TAP block group required additional analgesics in only 20% of cases (95% CI: 7-33%), as opposed to 68% in the control group (95% CI: 49-87%), signifying a significant reduction of 48 percentage points (p<0.01, 95% CI of the difference: 28-68%). Conclusion: The research presented here illustrates the heightened effectiveness of the TAP block in managing pain compared to traditional methods for patients having abdominal surgery. The noteworthy decrease in VAS scores, along with the reduced requirement for extra post-surgery pain relief, highlights the TAP block’s potential as an efficient method for controlling pain. Continued investigation is recommended to determine the best techniques and identify the specific patient groups that might gain the most from this innovative method, aiming to improve both comfort and recovery following surgery. Keywords: Elective C-section, VAS score, Abdominal surgery, Effectiveness